Knowledge and Behavior of a Group of Dentists towards Antibiotic Prescription to Pediatric Patients in Baghdad. (Mustansiria Dental Journal, 2023)
Aim:  To evaluate the knowledge and behavior of a group of dentists in Baghdad towards prescribing antibiotics to pediatric patients.Method: A Cross sectional study was conducted by an electronic self- administered questionnaire to dentists specialized in Preventive or Pediatric Dentistry, general dentists with certificate in Preventive and Pediatric and Preventive Dentistry and to general dentists working in health centers of Al-Resafa in Baghdad. Open-ended and closed-ended questions were directed to the dentists regarding the knowledge and behavior towards prescribing antibiotics to children.Results: (116) dentists responded to the questionnaire consisted of (36) specialized dentists in Pediatric or Preventive dentistry, (8) general dentists (certificate in Preventive and pediatric Dentistry) and to (72) general dentist. Most of the dentists with an age range from 21 to 30. Females constituted most of the sample (74.1%). General dentists represented the higher proportion (62.1%). Only (38.8%) of the dentists were self-educated whereas the medical websites seemed to be the main source (80.0%). Besides, only (13.8%) of total dentists have attended scientific medical course on antibiotics indications and/or resistance for the last two years. Amoxicillin was the main antibiotic prescribed for non-allergic children (75.9%), whereas Erythromycin and Azithromycin were prescribed for allergic children (73.3%). (42.2 %) of the sample prescribed antibiotics once per-week, while (13.8%) prescribed on need.  Cellulitis contributed (60.3%) among conditions need prescription of antibiotics before and/or after the treatment. Regarding the prophylactic antibiotics, high risk cardiac conditions represented (93.1%).Conclusion: Most of the general and specialist dentists were aware towards antibiotics prescription for children but lacked in updating their information which based primarily on their previous dental education.